The effectiveness of selected parameters of ultrasonic waves in the conservative treatment carpal tunnel syndrome - Kwolek, Andrzej; Zwolińska, Jolanta (European Journal of Clinical and Experimental Medicine, 2009)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Introduction: Carpal tunnel syndrome is one of the most common neuropathies in the upper limb on. It is a significant diagnostic and therapeutic problem. The aim of the study was to assess the effectiveness of the selected ultrasound wave parameters in conservative treatment of carpal tunnel syndrome. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Material and method: 61 people participated in the research. 102 hands were examined. Objects were assessed active and subjective clinical symptoms. Electroneurographic and computer examinations were performed measurement of the range of motion and strength of the hand squeezing. The patients were randomly assigned to one of three groups. Treat- did not include: ultrasound therapy, whirlpool massage and neuromobilization. In the first group, a continuous wave UD was applied with the intensity 0.3 I know, in the second group a continuous wave with the intensity 0.6 W / em ", and in In the third group, the impulse UD wave with the intensity of 0.6 I know ". The research was performed before the implementation of rehabilitation gram, after its completion and after one year. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Results: The obtained results indicate the effectiveness of the applied therapeutic program. Uses- statistically significant improvement in most of the symptoms tested was scanned. Assessment of treatment effects in depending on the type of ultrasonic wave used, it showed similar effectiveness of both intensively waves. Some of the assessed results obtained better results after sonication with the impulse wave parameters, although the differences demonstrated, except for pain experienced during the day, were not statistically significant. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Conclusions: Ultrasonic waves with intensities in the range of low and medium doses reduce increasing the severity of clinical symptoms, and the total amount of energy decides about the results of the therapy transferred to the tissues during the procedure. The beneficial effects of sonication are more pronounced after using impulse wave application.